Upcycling to Sustainably Reuse Plastics. Issue 25 (8th July 2021) - Zhao, Xin; Boruah, Bhanupriya; Chin, Kek Foo; Đokić, Miloš; Modak, Jayant M.; Soo, Han Sen
Abstract: Plastics are now indispensable in daily lives. However, the pollution from plastics is also increasingly becoming a serious environmental issue. Recent years have seen more sustainable approaches and technologies, commonly known as upcycling, to transform plastics into value‐added materials and chemical feedstocks. In this review, the latest research on upcycling is presented, with a greater focus on the use of renewable energy as well as the more selective methods to repurpose synthetic polymers. First, thermal upcycling approaches are briefly introduced, including the redeployment of plastics for construction uses, 3D printing precursors, and lightweight materials. Then, some of the latest novel strategies to deconstruct condensation polymers to monomers for repolymerization or introduce vulnerable linkers to make the plastics more degradable are discussed. Subsequently, the review will explore the breakthroughs in plastics upcycling by heterogeneous and homogeneous photocatalysis, as well as electrocatalysis, which transform plastics into more versatile fine chemicals and materials while simultaneously mitigating global climate change. In addition, some of the biotechnological advances in the discovery and engineering of microbes that can decompose plastics are also presented. Finally, the current challenges and outlook for future plastics upcycling are discussed to stimulate global cooperation in this field. Abstract : Plastics are mixed blessings that are convenient to our daily lives but have created a major environmental crisis. There are growing calls worldwide to reduce consumption, reuse more, recycle, and upcycle plastics. However, reducing, reusing, and recycling delay, rather than overcome the plastics problem. Here, more sustainable alternative approaches and technologies for plastics upcycling are reviewed.